Hubungan Pemahaman Tentang Bioteknologi Dengan Strategi Coping Stress Mahasiswa Tadris Biologi IAIN Kerinci Dalam Menerima Vaksin Covid-19 - Silvia Permata Sari; Dharma Ferry; Emayulia Sastria (Institut Agama Islam Negeri Kerinci, 2023)
The government's plan to vaccinate the Indonesian population for Covid-19 has encountered obstacles due to the emergence of hoaxes regarding the Covid-19 vaccine. Several students of Biology Department of IAIN Kerinci who have contracted biotechnology courses, that some of these students have not dared to be vaccinated against Covid-19 because they were affected by the Covid-19 vaccine hoax. The research was conducted on students who had contracted biotechnology courses at the Biology Department of IAIN Kerinci, using quantitative methods and correlational approaches. From the results of the study, it was found that the level of understanding of students' biotechnology was in a low category, namely 42.85% with a frequency of 27 respondents. Meanwhile, students' stress coping strategies in receiving the Covid-19 vaccine were in the high category, namely 84.12% with a frequency of 53 respondents. The results of the correlation analysis show a significance value of 0.007 and it means that there is a relationship between the two variables in this study, but the interpretation of the correlation is categorized as low with a correlation coefficient value of 0.335. This means that increasing understanding of biotechnology will affect the improvement of students' stress coping strategies in receiving the Covid-19 vaccine.